Efficiency decomposition in dealers from the perspectives of demand forecasting, sales force, and inventory control: a case study. Issue 16 (9th December 2016) - Yang, Fu-Chiang
Abstract: Efficiency decomposition is being able to know the most effective way to improve a company's organisational efficiency. This study proposes a network performance evaluation model with non-controllable variables to evaluate dealers with an emphasis on their internal processes, including demand forecasting, sales force and inventory control. The proposed model decomposes the organisational efficiency into a weighted average of internal process efficiencies, where the weights associated with the internal processes are data-driven. This is applied to an empirical case consisting of 27 automobile parts dealers in Taiwan. Based on the analysis results, dealers know the relative contribution of each internal process to the organisational efficiency, and inefficient dealers are assigned targets for enhancing the organisational efficiency as well as the process efficiencies.